The critical role of optimized energy density in controlling void morphology and enhancing mechanical properties of L-PBF Ti-6Al-4V ELI alloy - Supapat Trithepchunlayakoon; Aung Nyein Soe; Atikom Sombatmai; Suppakrit Khrueaduangkham; Vorapat Trachoo; Dinesh Rokaya; Patcharapit Promoppatum; Viritpon Srimaneepong (PLoS ONE, 2025)
Laser power is referred to as one of the critical process parameters governing the volumetric energy density in the Laser Powder Bed Fusion (L-PBF) process. The purpose of the study is to systematically investigate the influence of laser energy density on the void morphology, microstructure, and mechanical properties of the L-PBF printed parts which were fabricated with laser power ranging from 75 to 175 W. Comprehensive analysis of void defect was conducted by employing Archimedes’ method, optical microscope (OM), and X-ray microcomputed tomography (Micro-CT). Surface quality was analyzed by surface roughness measurement. Tensile testing was performed to establish the correlation between process parameters, material microstructure, and mechanical behavior in as-built samples. Under the optimal process parameters, this work achieved a minimum void fraction of 0.3%. At various laser energy densities, three distinct morphologies, namely lack of fusion (LOF), gas pores (GP), and keyhole (KH), were generated. Notably, LOF has a more detrimental effect on tensile characteristics, in comparison to GP and KH defects if laser power was less than 100 W. Interestingly, subsurface spherical pores at the hatch border demonstrate a less substantial influence on the tensile behavior of as-built samples than LOF. The correlation analysis revealed that the presence of void defects primarily influenced strength, modulus of elasticity, and strain at break. Energy density proved to play a pivotal role in defect generation, non-equilibrium microstructure, and mechanical properties of L-PBF. Based on our findings, selecting 100 W of laser power with a speed of 1200 mm/sec could be an optimal choice for achieving a satisfactory result in as-built L-PBF part.